Mobile robot position control in environment with static obstacles. Issue 2 (18th January 2021) - Giannousakis, Konstantinos; Tzes, Anthony
Abstract : This study addresses the problem of efficiently navigating a differential drive mobile robot to a target pose in a region with obstacles, without explicitly generating a trajectory. The robot is assumed to be equipped with an omnidirectional range sensor, while the region may or may not be a priori known. Given the known obstacles in each iteration of the controller, the shortest path connecting the robot and the target point provides a raw desired movement direction. Considering the unobstructed area in that direction, the size of the robot and the obstacle contours in its visibility range, the reference direction is determined. Finally, respecting the velocity and acceleration constraints of the robot, the angular velocity is properly selected to rotate the robot towards the reference direction, while the linear velocity is chosen to efficiently minimise the distance to the final target, as well as to avoid collisions. After the robot has reached the target, the controller switches to orientation mode in order to fix the orientation. Experimental studies demonstrate the effectiveness of the algorithm.